Removal of Total Petroleum Hydrocarbons (TPHs) and Polycyclic Aromatic Hydrocarbons (PAHs) in Spent Synthetic-Based Drilling Mud Using Organic Fertilizer - , Felix Obinduka; , Ify L. Nwaogazie; , Onyewuchi Akaranta; , Gideon O. Abu (Archives of Current Research International, 2018)
Treatment and disposal of spent (used) drilling mud have become an important environmental challenge in the oil and gas industry. Total Petroleum Hydrocarbons (TPHs) and Polycyclic Aromatic Hydrocarbons (PAHs) constitute the major contaminants in spent drilling mud. In this study, five spent synthetic-based drilling mud samples were collected from five oil fields in the Niger Delta. Samples collected on day 0 were analyzed for TPHs and PAHs. Concentrations higher than the permissible regulatory limits were recorded. The efficacy of urea fertilizer in the remediation of TPH-and PAH-impacted mud was investigated. Six sub-samples and six control sub-samples were tested bi-weekly for 12 weeks with 20 g, 25 g, and 30 g doses of urea fertilizer per 20 L of spent mud for each of the five samples representing each individual oil field (marked A through E). Removal of TPHs and PAHs with urea fertilizer treatment proved to be fast and efficient. In 6 weeks, with a dose of 1.5 g/L, over 98% removal of TPHs was recorded, and more than 94% of PAHs, and in 12 weeks, more than 99.5% removal was recorded for both. The residual levels of TPHs and PAHs met Department of Petroleum Resources (DPR: Nigeria) and US EPA limits for land disposal. Mathematical models with a goodness of fit (R2) of 0.999, were developed to predict the rate of the degradation processes.